Bridging the student funding gap in the Ministry of Higher and Tertiary Education, Science and Technology Development - Lewis, Teddy (Midlands State University, 2017)
The research was motivated by the researcher’s observation of the current tertiary student funding. A large number of tertiary students are dropping out of college because of lack of funding. The research was on “bridging the student funding gap in the Ministry of Higher and Tertiary Education, Science and Technology Development”. The main focus was on the challenges of the student funding system, solutions to those challenges and methods of bridging the student funding gap with a view to establishing the best practice. Literature from different scholars was discussed in this study so as to attain the objectives of the study. The research used both qualitative and quantitative research methods using questionnaires and structured interviews as research instruments. The analyses was made from the findings shows that the Student Cadetship Scheme is not sustainable. The rate on which arrears was ballooning are on a yearly basis was alarming, the issue of inadequate funding will continue and thereby widening the student funding gap. The study recommends that the policies on student funding that are sound must be formulated by the MHTESTD like cost sharing, loan and grant, loan and public private partnership.